Transformation of Farmer Resistance in Conservation Areas: Land Occupation by Farmers in Mount Halimun-Salak National Park, West Java - Sardjo, Sulastri; Dharmawan, Arya Hadi; Darusman, Dudung; Wahyuni, Ekawati Sri (Masyarakat: Jurnal Sosiologi, 2022)
A number of studies have shown various agrarian conflicts as a response by local farmers against the policy of national parks that prohibits them from accessing conservation forest areas. However, previous studies had not explained the dynamics of power relations between park authorities and farmers who stand in opposition to these policies. This study employs a qualitative research approach complemented by secondary data to explain the transformation of farmer resistance in the Mount Halimun-Salak National Park (TNGHS) area, namely from their repertoire of everyday resistance to practices of land occupation. Specifically, this study uses the “powercube” analytical framework to explain the process of this transformation. The study concludes that changes have occurred within the dimensions of peasant power. Regarding the space of power, the power of farmers was transformed from being strictly exerted within closed spaces to being more open (invited), which enables them to conduct negotiations with the park authorities. Meanwhile, farmers now exert their power at the local TNGHS area level, after previously only taking place within each household. Finally, the form of power has changed from being hidden to more visible, which allows them to acquire the “recognition” of TNGHS authorities as legitimate sharecroppers. Farmers have been able to occupy land by taking advantage of the political space provided by a period of democratization, as well as their ability to mobilize economic capital and forge social relations with various actors, including the TNGHS park authorities.